2018
DOI: 10.1097/yct.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation Effect of Low-Frequency Repetitive Transcranial Magnetic Stimulation Over Presupplementary Motor Area in Obsessive-Compulsive Disorder

Abstract: Low-frequency rTMS over pre-SMA may not be effective as an augmenting agent in partial/poor responders to SRIs. This study underlines the need to explore alternate rTMS protocols in OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
2
29
0
1
Order By: Relevance
“…Chistyakov et al used 1200 to 3600 pulses per session (600 pulses repeated and separated by a 15 min interval) and found a greater effect for the 3600 pulse (28). In the same way, other studies used a greater number of pulses (1200 to 1500) than we did (11)(12)(13)(14)(15)22). In our study, 600 pulses may not have been sufficient for inducing clinical effects.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Chistyakov et al used 1200 to 3600 pulses per session (600 pulses repeated and separated by a 15 min interval) and found a greater effect for the 3600 pulse (28). In the same way, other studies used a greater number of pulses (1200 to 1500) than we did (11)(12)(13)(14)(15)22). In our study, 600 pulses may not have been sufficient for inducing clinical effects.…”
Section: Discussionsupporting
confidence: 53%
“…In 2006, Mantovani et al (10) demonstrated that inhibition of the SMA successfully reduced OCD symptoms. Following this pioneering study, 5 randomized trials in OCD using low frequency rTMS over the SMA (11)(12)(13)(14)(15) reported inconsistent results. In the current trial, we used cTBS, known to induce larger and longer-lasting modulation of cortical excitability than standard rTMS (16), thus offering the promise of a potentially greater clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent trial demonstrated superior efficacy of this protocol over antipsychotic augmentation in treatment-resistant OCD subjects (Pallanti et al, 2016). However, given recent inconsistent reports on inhibitory rTMS protocols targeting the SMA (Arumugham et al, 2018;Harika-Germaneau et al, 2019;Pelissolo et al, 2016), there is a need for large multicentre trials to confirm its efficacy at this location.…”
Section: Treatment-resistant Obsessive-compulsive Disorder -Noninvasimentioning
confidence: 99%
“…[14] However, an RCT from our center involving 36 patients with refractory OCD failed to demonstrate any significant difference between active and sham low-frequency rTMS over bilateral pre-SMA. [15]…”
Section: Supplementary Motor Areamentioning
confidence: 99%